Violence Against Ahmadiyya as Productive Intolerance: Adressing Jeremy Menchikâ€™s Godly Nationalism - Rizkita, Muhammad; Riyanto, Waryani Fajar (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
This article examines godly nationalism using the theory of secularism. This connection is based on a shared "we-feeling" rooted in the common belief systems fostered by cooperation between the state and religious organizations (NU, Muhammadiyah, Persis). Jeremy Menchik argues that violence against Ahmadiyya should be viewed as "productive intolerance" rather than merely damaging democracy, as it is intended to protect this religious bond. The concept of godly nationalism has been criticized for neglecting religious freedom as a human right. This concept also overemphasizes macro-level data while failing to explain the local realities experienced by Ahmadiyya. The primary data for this research is Menchik's book titled "Islam and Democracy in Indonesia: Tolerance Without Liberalism,â€ then, it will be analyzed theoretically by borrowing Jose Casanova's secularism theory. This article found that the absence of secularism discourse throughout his work influenced his stance in understanding the nuances of religious intolerance in Indonesia. According to Menchik, Indonesia is viewed as a moderate country, but not in the form of binary opposition, as seen in the genealogy of secularism in the Western world, where religion is often positioned with certain negative prepositions.